STRATEGI PEMUKTAHIRAN DATA PEMILIH DALAM PEMILIHAN UMUM 2024 - Mutiara, Mutiara; Prianto, Andi Luhur; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is: To determine environmental observations for updating voter data in Salupangkang Village IV, Topoyo District, Central Mamuju Regency. This research uses qualitative methods. The type of research used is descriptive research. The results of the research show that the strategy for updating voter data has been said to be effective as seen in indicators 1. Environmental Observation which shows high awareness, commitment and readiness 2. Strategy Formulation for the importance of coordination between PPK, PPS and Village Government 3. Implementation of this strategy approach shows attention to an organized process, good budget management, 4. Overall evaluation and control, this approach reflects a commitment to involve all relevant parties in organizing elections.